2016
DOI: 10.1088/1674-4527/16/1/004
|View full text |Cite
|
Sign up to set email alerts
|

Global Mg/Si and Al/Si Distributions on the Lunar Surface Derived from Chang'E-2 X-ray Spectrometer

Abstract: X-ray fluorescence remote sensing technique plays a significant role in the chemical compositions research of the Moon. Here we describe the data analysis method for China's Chang'E-2 X-ray spectrometer (CE2XRS) in detail and present the preliminary results: the first global Mg/Si and Al/Si maps on the lunar surface. Our results show that the distributions of Mg/Si and Al/Si correlate well with the terrains of the Moon. The higher Mg/Si ratio corresponding to the mare regions while the lower value correspondin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The results from Chang'e 2 XRS (Dong et al, 2016) indicate lower mafic abundance compared to LPGRS results (Fig. 5).…”
Section: Other Mafic Abundance Results Setsmentioning
confidence: 77%
See 4 more Smart Citations
“…The results from Chang'e 2 XRS (Dong et al, 2016) indicate lower mafic abundance compared to LPGRS results (Fig. 5).…”
Section: Other Mafic Abundance Results Setsmentioning
confidence: 77%
“…The global median Al 2 O 3 found by Lunar Prospector's LPGRS, 24.7 wt% (Prettyman et al, 2006), implies a mafic abundance of 22.8%. The Chang'E-2 X-ray spectrometer (Dong et al, 2016) found 22.6 wt% Al 2 O 3 , implying for mafic abundance 27.4%, nearly three times the Kaguya SP result. The two X-ray result-sets essentially straddle the intermediate global result-set, LPGRS.…”
Section: Other Mafic Abundance Results Setsmentioning
confidence: 80%
See 3 more Smart Citations